Bagaimana Matematika Tumbuh Berdasarkan Pandangan Filsafat (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
Abstract. Some mathematicians say that the questions that arise from what we know predicts what progress we will make and what we will know in the future. In predicting the growth of mathematics, it is necessary to know what experiments have been carried out by mathematicians with the goals that can be achieved so that they can determine a prediction. This study aims to determine the development of mathematics based on a philosophical view. This research method is a literature study. The results of the study show that based on a philosophical view, the growth of mathematics begins when a problem arises regarding the limited existence of mathematical objects, so that there is a need for an expansion of the number system. The growth of mathematics is also based on the existence of mathematicians who find many of the same things and many of the same sequences. Therefore, mathematicians claim that they do not make a mathematics but they are as instruments for the discovery of mathematics itself.
Keywords: growing math; philosophy